It's the product not the polymer: rethinking plastic pollution - Stanton, Thomas; Kay, Paul; Johnson, Matthew; Chan, Faith Ka Shun; Gomes, Rachel L.; Hughes, Jennifer; Meredith, William; Orr, Harriet G.; Snape, Colin E.; Taylor, Mark; Weeks, Jason; Wood, Harvey; et al. (2020)
Mismanaged plastic waste poses a complex threat to the environments that it contaminates, generating considerable concern from academia, industry, politicians, and the general public. This concern has driven global action that presents a unique opportunity for widespread environmental engagement beyond the immediate problem of the persistence of plastic in the environment. But for such an opportunity to be realized, it is vital that the realities of plastic waste are not misrepresented or exaggerated. Hotspots of plastic pollution, which are often international in their source, present complex environmental problems in certain parts of the world. Here we argue, however, that the current discourse on plastic waste overshadows greater threats to the environment and society at a global scale. Antiplastic sentiments have been exploited by politicians and industry, where reducing consumers' plastic footprints are often confused by the seldom-challenged veil of environmental consumerism, or “greenwashing.” Plastic is integral to much of modern day life, and regularly represents the greener facilitator of society's consumption. We conclude that it is the product, not the polymer that is driving the issue of plastic waste. Contemporary consumption and disposal practices are the root of much of the anthropogenic waste in the environment, plastic, or not. Effective environmental action to minimize plastic in the environment should be motivated by changes in consumption practices, policies, and product design, and should be informed by objective science and legislation. This article is categorized under:. Science of Water > Hydrological Processes. © 2020 The Authors. WIREs Water published by Wiley Periodicals LLC.